1998
DOI: 10.1029/97jd02988
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoroacetic acid from degradation of HCFCs and HFCs: A three‐dimensional modeling study

Abstract: In this paper we present the global distribution of TFA in the gas phase and in precipitation produced by the degradation of HFC-134a, HCFC-124, and HCFC-123 using a coarse grid chemical transport model (CTM), but including synoptic scale weather patterns, diurnal boundary layers, and wet and dry convective plume mixing processes derived from a general circulation model (GCM). Observed climatological values of 5747

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 33 publications
(13 reference statements)
3
81
2
Order By: Relevance
“…Rainwater TFA levels TFA levels in collected rainwater samples ranged from 45.8 to 974 ng L −1 with a median concentration of 166 ng L −1 and an average of 225 ng L −1 (Fig. 2), exceeding annual average levels of about 120 ng L −1 as predicted for the year 2010 (Kotamarthi et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Rainwater TFA levels TFA levels in collected rainwater samples ranged from 45.8 to 974 ng L −1 with a median concentration of 166 ng L −1 and an average of 225 ng L −1 (Fig. 2), exceeding annual average levels of about 120 ng L −1 as predicted for the year 2010 (Kotamarthi et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a study in Switzerland reported an average TFA level of 151 ng L −1 in rainwater, but calculated rainfall-weighted average was 116 ng L −1 using their rainfall and TFA data (Berg et al, 2000). It should be noted that Kotamarthi et al (1998) for the year 2010, and higher rainwater TFA levels with a range from 150 to 200 ng L −1 occurred in the northern middle latitudes due to CF 3 COF converting to TFA with so short lifetime that production of TFA maximizes in these areas. In this study, the annual rainfallweighted average TFA level of 152 ng L −1 in Guangzhou fell within the range predicted by Kotamarthi et al (1998) for the year 2010 in the northern middle latitudes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations